Hydrogeochemical exploration for volcanic-hosted massive sulfide deposits in semi-arid Australia. Issue 2 (17th February 2018) - Gray, D. J.; Yeats, C. J.; Noble, R. R. P.; Reid, N.
ABSTRACT: Research on hydrogeochemistry for mineral exploration for inland Australia includes development of weathering models and extensive mine-scale and regional groundwater data. Mineral saturation indices for groundwater, activity–activity plots and reaction modelling simulate weathering of volcanic-hosted massive sulfide (VHMS) deposits in deeply weathered environments. At 10 m or more below surface, dissolved O2 is very low and other solutes such as sulfate, carbonate and nitrate are more likely oxidants. Modelling indicates that these processes differ from oxic weathering of highly eroded terrains, and provide the framework to develop robust hydrogeochemical exploration procedures in covered terrains. Sulfide weathering potentially occurs in two or more phases that effect surrounding groundwaters in differing manners. Deeper oxidative alteration of sulfides ( e.g. bornite to chalcopyrite), occurring tens to hundreds of metres below surface, uses sulfate and carbonate as oxidants, causing neutral to alkaline conditions. In this zone, only pyritic massive sulfides potentially generate acidic conditions. Thus, deep sulfide-rich rocks are indicated by sulfate-depleted groundwater. Closer to the surface, sulfides are oxidised to soluble sulfates by dissolved nitrate, with much less acid production than if dissolved oxygen was the main oxidant. Thus, in shallow groundwater, sulfides are indicated by sulfate enrichment and nitrate depletion. Elements are released from sulfides and wall rocks by acid or alkaline conditions. The derived FeS (pH–Eh + Fe + Mn) and AcidS (Li + Mo + Ba + Al) indices distinguish sulfide systems through tens of metres of cover. VHMS systems are distinguished from other non-economic sulfide deposits where there is little transported cover, using various dissolved elements, including Zn, Pb and Cu. Elsewhere, 'patchiness' and limited aerial extent of metal signals are due to adsorption effects, that intensify with depth. Other elements such as Mn and Co have lesser diminution effects, but are less selective indicators for VHMS. There is exploration potential for elements such as Pt or Ag. These varying sulfide indicators have moderate utility, even for large-scale (∼5 km spacing) sampling. Results indicate that hydrogeochemistry can add value to greenfields exploration for VHMS ore deposits in deeply weathered terrains. It is also moderately successful at indicating the presence of sulfide-rich systems (whether magmatic or hydrothermal) under >100 m cover, thus providing a rapid and cost-effective regional prospectivity tool for deeply buried terrains. Such mineral exploration tools will encourage exploration investment for more difficult regions of Australia and in other deeply weathered regions of the world.